GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN REMAJA PUTRI TENTANG PENANGANAN DISMENORE PRIMER DI SEKOLAH MENENGAH PERTAMA PGRI 5 DENPASAR - Meidyanti S, Putu Ayu Yurika; Sriasih, Ni Gusti Kompiang; Darmapatni, Made Widhi Gunapria (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Primary dysmenorrhea is a symptom that arises due to abnormalities in the pelvic cavity which can interfere theactivities of school-age teenegers. More than 50% of women in the world are suffered from dysmenorrhea and the number of cases of dysmenorrhea in Indonesia is 60 % -70%. Approximately 90 female students of SMP PGRI 5 Denpasar are suffered from primary dysmenorrhea. The purpose of the study is to determine the knowledge, attitudes and actions of teenege girls regarding the management of primary dysmenorrhea. This type of research is descriptive quantitative with cross sectional research design. The sample in this study is 22 respondents. This study used a proportionate stratified random sampling technique. The instrument used in this study was a questionnaire made by the researcher. The results of the study is most of the respondents have sufficient level of knowledge, more than half of the respondents have a negative attitude and more than half of the respondents have unfavorable actions. The school is expected to improve the UKS and KSPAN facilities and programs as well as provide counselling using interesting media regarding reproductive health especially primary dysmenorrhea. Keywords:  knowledge, attitudes, actions, primary dysmenorrhea